On taxes and suspicion: Ambivalences of rule and the politically possible in contemporary Hargeisa, Somaliland - J. Antonio Campos (Danish Institute for International Studies (DIIS), 2016)
In the city of Hargeisa, tax collectors and fiscal officers of the self-proclaimed and internationally unrecognized Republic of Somaliland exhibit a constant ambivalence as they perform their job, i.e., direct income taxation. While presuming the taxpayer's dishonesty, they rely on the anticipation of honesty to collect public revenue, although they could deploy state force to accomplish their task. Ethnographic material collected over six months of fieldwork is used in this paper to argue that this ambivalence and the hesitancy to use violence can be analytically construed as a ground from which a form of political obligation other than fear of state violence may eventually emerge. The tax collectors and I, based on literary theory, decided to speak about this ambivalence as "suspicion", for this feeling enables the awareness of unfolding time and thereby opens up a future horizon where the possibility of genuine adherence to the Somalilander project emerges. In this sense, the tax collector's suspicion in Hargeisa reflects the Somalilander quest to retrieve the proper foundations of its political authority. Taxes, thus, have a dual meaning: when imagined as debt, they construe collectors as the authority of the sovereign nation state; when imagined as a form of owing, they construe collectors as agents of a common collective project. The central point of this study is that this second path of the moral imagination could hold the promise of a distinct political future not rooted in coercion. This future flashes for a moment in the fiscal situation before the attentive observer.
Keywords: 330